Biodegradable Indocyanine Green Nanoprobe for In vitro Early Tumor Diagnosis - (:unkn) unknown (IEEE, 2018)
Advanced biomedical imaging techniques, intelligent drug designs and controlled drug release studies let patients can be safeguarded via early detection of cancerous cells without damaged to healthy cells. In this study, the ICG nanoprobe was fabicated via co-axial electrospinning method by encapsulating of ICG, which has high light absorption and emission in the near infrared region (NIR), in biocompatible and biocompatible Poly(epsilon-caprolactone) (PCL) polymer. During co-axial fiber formation, in order to understand of the physical effect of ICG solution onto pure PCL solution, viscocity, electrical conductivity, density and surface tension were characterized before co-axial electrospinning process. The high electrical conductivity and low viscosity of ICG, caused the PCL/ICG nanofiber diameters (Phi=627.15 +/- 157.77 nm) decreased compared to pure PCL nanofibers (Phi)=930.71 +/- 210.27 nm). Encapsulated ICG dye in the PCL nanofiber was determined by FT-IR and confocal microscopy. Controlled ICG release from PCL / ICG nanofibers was performed up to 21 days in PBS (pH 7).
Keywords: Poly(epsilon-caprolactone); Indocyanine Green; Nanofiber; Co-axial Electrospinning; Encapsulating; Nanoprobe